Enhancing Firm Value : The Role of Profitability as Moderation - Ayu Sarah Sulistyawati; Dwi Ratmono (Jurnal ASET (Akuntansi Riset), 2023)
Financial conditions are insufficient to guarantee the firm value to grow and develop in a sustainable method. If the corporation also considers the social and environmental aspects of life, its sustainability will be ensured. This research aims to analyze the effect of environmental social governance (ESG) and dividend policy on firm value with profitability as a moderating variable in 31 companies with 186 annual report data of Indonesian companies listed on Bloomberg in 2015-2020. All data were analyzed using SEM-PLS (Structural Equation Modeling based on Partial Least Square) with SmartPLS 3.0 application. The results proved that ESG has a significant negative effect on firm value. On the contrary, dividend policy gradually improved firm value. Another finding showed that The impact of the dividend policy on firm value could be mitigated by profitability, while profitability was not capable to moderate the effect of ESG on firm value. The research implication for the company is to increase the firm value. Therefore, The industry orientation emphasizes both financial and non-financial success. This research develops previous research with several differences. First, adds the independent variable, namely the dividend policy, Second, adding the profitability variable as research moderating variable and proxies used in firm value are the PBV research